Consulting on the inside : an internal consultant's guide to living and working inside organizations - Scott, Beverly (American Society for Training and Development AlexandriaUS, 2000)
Defines internal consulting and addresses challenges and opportunities for internal consultants. Advises on overcoming roadblocks within oneself as well as within the organization. Discusses what it takes to excel, and provides a detailed and practical 8-phase consulting process guide for new internal consultants. Includes models, checklists and tools.